PsAAT3, an oomycete-specific aspartate aminotransferase, is required for full pathogenicity of the oomycete pathogen Phytophthora sojae. Issue 4 (April 2016) - Wang, Rongbo; Zhang, Meixiang; Liu, Hong; Xu, Jing; Yu, Jia; He, Feng; Zhang, Xiong; Dong, Suomeng; Dou, Daolong
Abstract: Pathogen nutrient acquisition and metabolism are critical for successful infection and colonization. However, the nutrient requirements and metabolic pathways related to pathogenesis in oomycete pathogens are unknown. In this study, we bioinformatically identified Phytophthora sojae aspartate aminotransferases (AATs), which are key enzymes that coordinate carbon and nitrogen metabolism. We demonstrated that P. sojae encodes more AATs than the analysed fungi. Some of the AATs contained additional prephenate dehydratase and/or prephenate dehydrogenase domains in their N-termini, which are unique to oomycetes. Silencing of PsAAT3, an infection-inducible expression gene, reduced P. sojae pathogenicity on soybean plants and affected the growth under N-starving condition, suggesting that PsAAT3 is involved in pathogen pathogenicity and nitrogen utilisation during infection. Our results suggest that P. sojae and other oomycete pathogens may have distinct amino acid metabolism pathways and that PsAAT3 is important for its full pathogenicity.